EVOLUSI TEKTONIK DI DAERAH NENAS DAN KEFAMENANU, NUSA TENGGARA TIMUR IMPLIKASINYA TERHADAP POTENSI PERANGKAP (TRAP) HIDROKARBON PADA CEKUNGAN TIMOR BAGIAN BARAT - Alfiansyah, Arif; Nugroho, Hadi; Fahrudin, Fahrudin; Wahyudiono, Joko (Geological Engineering E-Journal, 2014)
In Timor island found many indications of hydrocarbons such as oil seeps, gas seeps and mud volcanoes. In the eastern part of the territory there are indications of more oil, while in the western part of the territory more gas indications (Charlton, 2001). It is a challenge for a geologist in particular to uncover all the potential that exists in the Timor Basin.The purpose of this study was to determine the composition of the stratigraphy in the study area, which is developing the geological structure and its relationship with the existing stratigraphy in the study area, the main emphasis is to work towards the western part of Timor Island, Explaining the tectonic evolution of the study area and type of trap hydrocarbons that exist in the study area.The method used in this thesis is a survey method and analysis methods. Methods of geological mapping survey with a description of the characteristics of each formation encountered and measured thick layer of rock that is useful for stratigraphic cross sections, and measurement of structural elements such as bedding plane, joint, faults and folds. Analysis method by analyzing both the geological structure alignment analysis and analysis stereografis.The composition of the regional stratigraphic in research area from old to young is Maubise Formation, Atahoc Formation, Cribas Formation, Niof Formation, Babulu Formation, and Aitutu Formation. Geological structures that developed in the study area at Permian old rocks there are a reverse fault has trending NW-SE, strike slip fault has trending N-S, and normal fault has trending NW-SE, whereas in Triassic old rocks there are a reverse fault has trending NE-SW, strike slip fault has trending NE-SW, and normal fault has trending NE-SW. Look at the similarity of hasÂ  trending reverse fault and normal fault orientation at Permian age, interpreted that reverse fault is result of reactivation from normal fault plane with same plane orientation. This also applies to Niof Formation, Babulu Formation and Aitutu Formation are Triassic old rocks there are a reverse fault has trending NE-SW and normal fault has trending NE-SW. the similarity of that trending orientation can interpreted as a result from reactivation of that happened at Permian old rocks. The main stress in Permian old rocks is NE-SW, while in Triassic old rocks is E-W. Based on analysis, trap hydrocarbon potential is structural trap with type are anticline and reverse faultÂ